On the Role of Transferrin in 67Ga Uptake by Tumor Cells - Anghileri, L. J.; Thouvenot, P.; Brunotte, F.; Robert, J. (Nuklearmedizin - NuclearMedicine, 1988)
In vitro uptake of 67Ga-citrate and 59Fe-citrate by DS sarcoma cells in the presence of tumor-bearing animal blood plasma showed a dramatic inhibition of both 67Ga and 59Fe uptakes: about ii/io of 67Ga and 1/5o of the 59Fe are taken up by the cells. Subcellular fractionation appears to indicate no specific binding to cell structures, and the difference of binding seems to be related to the transferrin chelation and transmembrane transport differencesDie In-vitro-Aufnahme von 67Ga- Zitrat und 59Fe-Zitrat durch DS-Sarkomzellen wurde in der Gegenwart von Blut tumortragender Tiere erheblich sowohl für 67Ga als auch für 59Fe unterdrückt: etwa 1/10 von 67Ga und ‘1/50von 59Fe wurden von den Zellen aufgenommen. Die subzelluläre Fraktionierung schien keine spezifische Bindung an Zellstrukturen aufzuzeigen und die Bindungsunterschiede schienen eine Beziehung zur TransferrinChelatbildung und zu transmembranösen Transportunterschieden aufzuweisen.